Regulation of apoptosis and differentiation by P53 in human embryonic stem cells - Grandela, Ana Catarina Martins (2008)
Tese de doutoramento em Biologia (Biologia Molecular) apresentada à Fac. de Ciências e Tecnologia da Univ. de Coimbra